1996
DOI: 10.2527/1996.7461256x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of subcutaneous adipose tissue from male calves at different stages of growth.

Abstract: The objective of this investigation was to compare fatty acid composition of calves from Bos taurus and Bos indicus cows across different stages of growth. Hereford (H) and Brahman (B) embryos were transferred to H or B cows (n = 58) to produce purebred Brahman (BB), purebred Hereford (HH), Hereford x Brahman (HB), and Brahman x Hereford (BH) offspring. Calves were castrated at 2 to 3 wk of age. Before weaning (210 d of age), calves were fed native grasses. After weaning, calves were fed a concentrate diet in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
3
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 25 publications
4
43
3
2
Order By: Relevance
“…Breed differences and associated effects of maturity or growth potential on the subcutaneous or intramuscular fatty acid composition of beef were also reported by Gillis et al [28], Huerta-Leidenz et al [32,33], Malau-Aduli et al [45,46], Mills et al [52], Pitchford et al [63], Rule et al [73] and Siebert et al [80]. Sex effects are also reported regularly.…”
Section: Beefmentioning
confidence: 52%
“…Breed differences and associated effects of maturity or growth potential on the subcutaneous or intramuscular fatty acid composition of beef were also reported by Gillis et al [28], Huerta-Leidenz et al [32,33], Malau-Aduli et al [45,46], Mills et al [52], Pitchford et al [63], Rule et al [73] and Siebert et al [80]. Sex effects are also reported regularly.…”
Section: Beefmentioning
confidence: 52%
“…MP has a high correlation with fatty acid composition and there are reports that fatty acid composition is influenced by sex and age. These studies have confirmed that the fat of heifers tends to be more unsaturated than the fat of steers (Yoshimura and Namikawa, 1985;Zembayashi et al, 1995) and aging increases MUFA (Huerta-Leidenz et al, 1996). Furthermore, effects of breed differences are also reported; purebred Wagyu cattle or the other breeds derived from Wagyu generally tend to have higher proportions of unsaturated fatty acids than other breeds (Yoshimura and Namikawa, 1985;May et al, 1993).…”
Section: Phenotypic Measurementsmentioning
confidence: 65%
“…Fatty acid composition is influenced by sex (Yoshimura and Namikawa, 1985;Zembayashi et al, 1995), diet (Melton et al, 1982;Mandell et al, 1998) and age (Huerta-Leidenz et al, 1996). Genetic influences, such as breed (Yoshimura and Namikawa, 1985;May et al, 1993) and sire (Xie et al, 1996), have also been reported, including sire-based differentiation in Japanese Black cattle (Oka et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, a decline in meat quality, especially meat tenderness, when B. indicus are compared with B. taurus has been widely documented (Wheller et al 2001), and B. indicus also tends to have a slower growth rate than B. taurus (Ferraz & Felicio 2010). Still, results regarding genetic differences in lipid profiles between zebuine and taurine cattle are scarcer, but there are indications that fatty acid profiles differ between B. taurus and B. indicus (Huerta- Leidenz et al 1996). However, these differences are largely dependent on the finishing system used, such that, with grain finishing, meat from B. indicus has higher levels of SFA, but that is not the case with pasture finishing (Bressan et al 2011).…”
Section: Introductionmentioning
confidence: 99%